2009
DOI: 10.1364/ao.48.006159
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of multiple photon scattering in sugar maple tree canopies

Abstract: Detecting objects hidden beneath forest canopies is a difficult task for optical remote sensing systems. Rather than relying upon the existence of gaps between leaves, as other researchers have done, our ultimate goal is to use light scattered by leaves to image through dense foliage. Herein we describe the development of a Monte Carlo model for simulating the scattering of light as it propagates through the leaves of an extended tree canopy. We measured several parameters, including the gap fraction and maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…For example, North [43] suggests for Sitka spruce a leaf angle distribution, (0.15 0.20 0.18 0.15 0.13 0.09 0.05 0.03 0.02), in 10 • increments from 0 • -90 • to the LiDAR axis. For Lambertian reflectance, the reflected light intensity would be proportional to the cosine of the LiDAR to surface normal angle, but Kaasalainen and Rautiainen [44] have shown that this is not a particularly good model for individual pine needles, as Greiner et al [45] did for maple leaves. For the pine needles, there is no convenient analytic expression, but it was observed, for example, that there was a significant increase in measured needle brightness (1.13-1.79) at 0 • compared to 3 • -4 • which is suggestive of significant specularity.…”
Section: B Determining the Ndvi Profile In Comparison With The Labora...mentioning
confidence: 99%
“…For example, North [43] suggests for Sitka spruce a leaf angle distribution, (0.15 0.20 0.18 0.15 0.13 0.09 0.05 0.03 0.02), in 10 • increments from 0 • -90 • to the LiDAR axis. For Lambertian reflectance, the reflected light intensity would be proportional to the cosine of the LiDAR to surface normal angle, but Kaasalainen and Rautiainen [44] have shown that this is not a particularly good model for individual pine needles, as Greiner et al [45] did for maple leaves. For the pine needles, there is no convenient analytic expression, but it was observed, for example, that there was a significant increase in measured needle brightness (1.13-1.79) at 0 • compared to 3 • -4 • which is suggestive of significant specularity.…”
Section: B Determining the Ndvi Profile In Comparison With The Labora...mentioning
confidence: 99%